A Washback Study on Portfolio Assessment - Kamalia Hakim, Putri; Srisudarso, Mansyur (ELT in Focus, 2020)
The latest developments in the field of learning English as a foreign language have encouraged language teachers to use more authentic and realistic assessments. This situation makes portfolios as alternative assessments increasingly popular. As the popularity of the portfolio grows, questions among assessment developers have also arisen. They question whether the portfolio really is a proper assessment. In this study, the researcher investigated the wash-back effect of portfolio-based assessment. She observed the instructional process in a translation and a writing class to see how the two types of portfolios were used. This qualitative analysis study also studies by triangulating the data with the support of data from interviews and questionnaires. Researcher then classified the opinions and reflections of students and lecturers obtained from the interview and questionnaire responses. The findings suggest the use of a portfolio is indeed appropriate for use in writing and translating subjects. Portfolio-based assessments generate positive washback effect on the learning process.